Student feedback on an online group used to support a Medical Humanities module in a Nepalese medical school - Shankar, PR; Piryani, RM (Journal of College of Medical Sciences-Nepal, 2012)
Background: An online Google group was created to supplement a Medical Humanities module at KISTMedical College. Objectives: The present study was carried out to understand student perceptions about the online group, understand factors preventing its widespread use and obtain suggestions for improvement. Method: The study was carried out among first year undergraduate medical students. They were explained the aims and objectives of the study and invited to participate after obtaining written, informed consent. Student feedback was collected in the form of their responses to a set of 10 questions about the online group. The responses were analyzed and common ones tabulated. Results: Fifty-eight of the 75 students participated. Forty-nine students were aware of the group. Only 10 respondents were group members. The group was regarded as a virtual grouping for sharing ideas about Medical Humanities and could provide knowledge about the subject and act as a backup resource in case students were unable to attend a session. The group was felt to be unsuccessful. Problems of internet access, load shedding and problems of managing time were hindering factors. Better publicity about the group, demonstrating the group during Wednesday’s session and making students utilize the group by submitting assignments through it were suggested. Conclusions: The KISTMC MH group was not successful and steps for improvement must be taken in future sessions. Major reasons hindering use of the group were mentioned. The issue should be further explored as online groups are an important means to support curricular initiates in medical schools. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 79-85 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6734